2014
DOI: 10.1161/strokeaha.114.005960
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hospital, Community, and Indirect Costs of Stroke Associated With Atrial Fibrillation

Abstract: A trial fibrillation (AF) increases the risk of stroke, disability, dementia, and death, with a characteristic profile of more severe, disabling, and recurrent stroke compared with stroke without AF. [1][2][3][4] With aging populations, the prevalence of AF is projected to increase ≥2-fold by 2050, accompanied by an increase in the frequency of AF-associated stroke. 5 Accurate health economic data are important to inform health policy decisions to respond to this societal increase in AF prevalence, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
0
33
1
Order By: Relevance
“…The hospital and residential care costs amounted to US $20,037 and US $16,148, respectively. Moreover, our cost estimates are significantly lower than the estimates made by Hannon et al [11], who investigated the costs of stroke associated with AF among 177 patients in Ireland. They estimated the average 2-year costs associated with AF-strokes to be US $76,602 in 2007 prices, including acute hospital, nursing home, community health care, and indirect costs.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The hospital and residential care costs amounted to US $20,037 and US $16,148, respectively. Moreover, our cost estimates are significantly lower than the estimates made by Hannon et al [11], who investigated the costs of stroke associated with AF among 177 patients in Ireland. They estimated the average 2-year costs associated with AF-strokes to be US $76,602 in 2007 prices, including acute hospital, nursing home, community health care, and indirect costs.…”
Section: Discussioncontrasting
confidence: 73%
“…We found only two large studies on the costs of stroke in patients with AF, and these studies included only hospital costs [8,9]. Previous studies have shown that the costs of stroke are higher in patients with AF than in patients without AF [8][9][10][11]. Additional studies are needed to ensure that valid cost estimates can be used to strengthen the foundation for evidence-based decision making regarding the treatment of AF and prevention of future strokes.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,[19][20][21] We acknowledge that our methodology for calculating the cost might be inaccurate, but the value is close to that reported in recent literature. 22 A list of all parameters and their values is presented on the On-line Table. There are several assumptions made in this model:…”
Section: Costs and Outcomesmentioning
confidence: 99%
“…Only two of the 15 studies discounted the cost at certain rates, therefore the reported cost may not be an accurate reflection of actual cost. Indirect costs were only reported in a small proportion of studies 24,44,45 , which would hinder the overall cost estimation required for an assessment from the societal perspective. For labor market outcomes, the lack of research on the relevant costs of productivity loss 44,45 is also apparent.…”
Section: Discussionmentioning
confidence: 99%
“…The median LOS estimate reported from these studies was 15.5 days per episode. The longest median LOS of 21 days (IQR: 60 days) was in Ireland 24 , while an average LOS of 5.2 days for non-repeated stroke admissions and 6.8 days for repeated stroke admission in the USA were reported as the shortest 25 among the included studies.…”
Section: Hospital Lengths Of Staymentioning
confidence: 99%